Isu Modernitas dan Ketidaksetaraan Gender pada Novel Tenggelamnya Kapal Van Der Wijck dan Para Priyayi serta Relevansinya dalam Pembelajaran Apresiasi Prosa - Rosidah, Siti Zulfah; Widanarti, Widanarti; Syarifatul Ainiyyah, Zuvika Amoret; Nurholis, Nurholis (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This research aims to identify the issues of modernity and gender equality raised in Indonesian muslim literature, specifically in the novels Tenggelamnya Kapal van der Wijck by Hamka and Para Priyayi by Umar Khayam. This research applies a descriptive qualitative methodology. The issue of gender inequality is particularly highlighted in the novel Tenggelamnya Kapal van der Wijck, as exemplified by the character of Hayati. Discrimination against women is depicted in the novel Tenggelamnya Kapal van der Wijck. Umar Khayam's Para Priyayi explores the contemporary manifestation of traditionalism in Indonesian religious practice, particularly within the context of Javanese Muslim society. The synthesis of Javanese tradition and modernity in Para Priyayi represents a contemporary phenomenon.